Beyond the Lantern Festival: Designing Fantasy Illustrations Inspired by Lontong Cap Go Meh and Kelenteng Hok An Kiong - Sutanto, Shienny Megawati; Mudra, I Wayan; Udayana, A. A. Gde Bagus; Suardina, I Nyoman (Universitas Ciputra, 2024)
This study examines the creative process behind the illustrations of the fantasy novel